Gestión de cobranza y su incidencia en la liquidez de la Cooperativa San Antonio, sucursal La Unión - Contreras Cox, Ginger de la Cruz (2020)
The present case study had the objective of analyzing the collection management and its impact on the liquidity of the cooperative of savings and credit ltda. The union branch in the years 2017 and 2018, the method was used, inductive and also It was necessary to apply the interview technique to the executives of the same, especially in the collection area of the entity in order to comply with the object of study and to be able to determine the existing shortcomings in said area. For this, an on-site investigation was carried out because the information obtained was provided by the Institution's financial department. It was necessary to apply financial ratios to measure the delinquency level where the unproductive portfolio and the total of the general portfolio were taken into consideration according to each year to establish the respective comparison and interpretation of the results obtained, as well as for the calculation of the liquidity, the value of the available funds and the total of short-term deposits were used according to each year under study, data that were taken from the Balance Sheet of the Cooperative and to establish a conclusion of the applied indicators, the limits established by the Superintendency of Popular and Solidarity Economy according to the segment to which the entity belongs. With the research process, the main objective of this study was reached and it was determined that there is a direct impact on the liquidity of the Cooperative and the Collection Management applied.